Relative fuel value of some coals on the Kansas markets - Nygard, Jens (My University, 1905)
Introduction: AIM AND OBJECT. The importance of coal as fuel in the factory, railroad, and home warrants the expending of time and effort in securing information that will give it a more intelligent use, and its consumer a more scientific basis for choosing his variety of coal. As yet coal is practically without a rival. The more important question then is: How does one variety of coal compare with another? and not: How does coal in general compare with other fuels? The prices of coals are based on the cost of mining and transportation, and sometimes on the caprices of the dealer. In the fixing of such prices little or no attention is paid to the worth of the coal as a fuel, and if the prices and values of coals are concordant it is wholly coincidental. The error of such a method in fixing the price -list is wholly obvious, and has led many to undertake to give to the consumer information that should enable him to secure the greatest value for his money when purchasing coal. The writer limits his observations to the more common coals handled by Kansas dealers. Most of these are mined in or near our own state, and only meet with successful competition by coals handicapped by the increased expense of a long shipment, in such services as for which the native coals are poorly adapted. GENERAL DESCRIPTION OF COAL. The samples of most of the coals tested were secured from the bins of the Higginbotham Fuel Co., of Manhattan, Kansas, and the writer is indebted to them for many of the facts and figures herein contained.
Citation: Nygard, Jens. Relative fuel value of some coals on the Kansas markets. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Anthracite; Bituminous; Rugby Coal; Lexington; Theses